PENINGKATAN KADAR HEMOGLOBIN (Hb) PADA IBU HAMIL DENGAN ANEMIA DENGAN KONSUMSI JUS JAMBU BIJI (PSIDIUM GUAJAVA. L ) - Neneng Siti Lathifah; Zarma H; Nurul Isnaini (JKM (Jurnal Kebidanan Malahayati), 2021)
IMPROVEMENT OF HEMOGLOBIN (Hb) LEVELS IN PREGNANT WOMEN WITH ANEMIA WITH THE CONSUMPTION OF JAMBU SEEDS (PSIDIUM GUAJAVA. L) ABSTRACT Background Anemia in pregnancy is a national problem because it reflects the socio-economic condition of the community and its influence is very large on the quality of human resources. The incidence of anemia in pregnant women 2018 in Pesisir Barat Regency is 29.9%. The incidence of anemia in pregnant women at Krui Health Center is 67.5%. The purpose of this study is to know the effect of giving guava juice (Psidium Guajava. L) to the increase of hemoglobin (Hb) levels in pregnant women with anemia in Krui health center in 2019.Methods Quantitative Research Type, the research design is a quasi-experimental method with a Non-equivalent Control Group Design approach. The population in this study were as many as 60 second trimester pregnant women and third trimester who had anemia, a sample of 30 pregnant women. 15 people were given treatment with guava fruit juice and Fe tablets, and 15 people were given treatment with Fe tablets, with inclusion criteria Willing to be respondents, Willing to consume guava juice, Pregnant women with mild and moderate anemia with hemoglobin levels (Hb 7.9 - 10 g / dl). With purposive sampling sampling technique. Analyze data with T-test (univariat and bivariat).The results showed an average hemoglobin level before consumption of guava juice and Fe tablets of 9.72 gr / dl, the average hemoglobin level after consumption of guava juice and Fe tablets was 11.13 gr / dl, the average hemoglobin level before consumption of Fe tablets of 9.80 gr / dl, the average hemoglobin level after consumption of FE tablets was 10.60 gr / dl. Conclusion It was known that there was an effect of giving guava juice (Psidium Guajava. L) to Hb levels in pregnant women with anemia in Krui Public Health Center, West Coast District in 2019. The results of the t test were p value 0,000 <α (0.05).Suggestion  It is recommended for health workers, especially midwives, to encourage pregnant women to consume guava juice as a companion to Fe because it can raise hemoglobin levels in pregnant women. Keywords              : Guava Juice, Tablets Fe, Hemoglobin Level ABSTRAK Latar Belakang Anemia pada kehamilan merupakan masalah nasional karena mencerminkan keadaan sosial ekonomi masyarakat dan pengaruhnya sangat besar terhadap kualitas sumber daya manusia. Angka kejadian anemia pada ibu hamil tahun 2018 di Kabupaten Pesisir Barat adalah sebesar 29,9%. Angka kejadian anemia pada ibu hamil di Puskesmas Krui sebesar 67,5%.Tujuan dari penelitian ini adalah diketahui Pengaruh Pemberian Jus Jambu Biji (Psidium Guajava. L) Terhadap Peningkatan Kadar Hemoglobin (Hb) pada Ibu Hamil dengan Anemia di Puskesmas Krui Tahun 2019.Metode Jenis Penelitian Kuantitatif, rancangan penelitian metode quasi eksperimen dengan pendekatan Non-equivalent Control Group Design. Populasi dalam penelitian ini adalah sebanyak 60 orang ibu hamil trimester II dan trimester III yang mengalami anemia, Sampel sebanyak 30 ibu hamil. 15 orang diberikan perlakuan dengan jus jambu biji dan tablet Fe, dan 15 orang diberikan perlakun dengan tablet Fe, dengan kriteria inklusi Bersedia menjadi responden, Bersedia mengkonsumsi jus jambu biji, Ibu hamil dengan anemia ringan dan sedang dengan kadar hemoglobin (Hb 7,9 – 10 g/dl). Dengan teknik sampling purposive sampling. Analisa data dengan uji T-test (univariat dan bivariat).Hasil penelitian menunjukan rata-rata kadar hemoglobin sebelum konsumsi jus jambu biji dan tablet Fe sebesar 9,72 gr/dl, rata-rata kadar hemoglobin setelah konsumsi jus jambu biji dan tablet Fe sebesar 11,13 gr/dl, rata-rata kadar hemoglobin sebelum konsumsi tablet Fe sebesar 9,80 gr/dl, rata-rata kadar hemoglobin setelah konsumsi tablet Fe sebesar 10,60 gr/dl.Kesimpulan Diketahui Ada Pengaruh Pemberian Jus Jambu Biji (Psidium Guajava. L) Terhadap Kadar Hb pada Ibu Hamil dengan Anemia di Puskesmas Krui Kabupaten Pesisir Barat Tahun 2019. Hasil uji t didapat p value 0,000 < α (0,05).Saran bagi tenaga kesehatan khususnya bidan agar menganjurkan kepada ibu hamil untuk mengkonsumsi jus jambu biji sebagai pendamping Fe karena dapat menaikkan kadar hemoglobin pada ibu hamil. Kata Kunci            : Jus Jambu Biji, Tablet Fe, Kadar hemoglobin